2020
DOI: 10.29328/journal.afns.1001023
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits and lifestyle changes during the COVID-19 lockdown: A comparative study (before and during isolation) on the 9 de Julio city (Buenos Aires, Argentina) population

Abstract: Following the COVID-19 proliferation beyond China’s borders at the beginning of 2020, containment measures have been taken by different countries around the globe. Citizens were forced to stay at home. Specifically, on March 19th, the Argentine Government decided to implement the “Social, preventive and mandatory isolation”, strategy that unfortunately impacts on the lifestyle, the practise of physical activity and on the nutritional aspect of the population. The aim of this study was analize eating habits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…These changes can be attributed to either a willingness to improve one's diet or to a disruption of eating habits caused by the temporary closure of workplace restaurants and the restriction of food premises' operating hours (hence reduced eating out). These results are consistent with previous research from other countries, which found improved diet quality during the lockdown in certain population subgroups (Alhusseini & Alqahtani, 2020;Giacalone et al, 2020;Miriam et al, 2020;Wang et al, 2021;Zielinska et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…These changes can be attributed to either a willingness to improve one's diet or to a disruption of eating habits caused by the temporary closure of workplace restaurants and the restriction of food premises' operating hours (hence reduced eating out). These results are consistent with previous research from other countries, which found improved diet quality during the lockdown in certain population subgroups (Alhusseini & Alqahtani, 2020;Giacalone et al, 2020;Miriam et al, 2020;Wang et al, 2021;Zielinska et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The COVID-19 (2019-2020) outbreak has had widespread impact to date effects on most people's lifestyles and working environments. Countries and cities are still being closed down in order to encourage social distance and to prevent excessive gatherings, thereby limiting the spread of COVID-19 (Miriam et al 2020). Even programmes that were previously taught in-person have rapidly shifted to online learning in order to meet educational obligations and avoid delaying students graduation, further education, and employment (Isaias, Sampson, and Ifenthaler 2021).…”
Section: Introductionmentioning
confidence: 99%